Dinamika Radikalisme di Pesantren: Tinjauan terhadap Isu dan Tantangan - Ardianto, Risko Aris; Ansori, Isa (TSAQOFAH, 2024)
Islamic boarding schools, known as pesantren, play a crucial role as traditional Islamic educational institutions in Indonesia and have been a focal point in discussions surrounding radicalism. This research aims to uncover the dynamics of radicalism that may occur within the pesantren environment and analyze the contributing factors to the spread of radical ideologies among the students. The research methodology employs a qualitative approach with data collection techniques including interviews, observations, and content analysis of relevant literature. The findings indicate that while pesantren play a significant role in shaping Islamic character and identity, they are also susceptible to the influence of radical ideologies. Factors such as economic inequality, social dissatisfaction, and a lack of inclusive education contribute to the emergence of radical attitudes among the students. Addressing the challenge of radicalism in pesantren involves enhancing understanding of moderate Islamic teachings, strengthening critical education, and fostering collaboration among the government, society, and pesantren. Prevention efforts should also focus on improving the well-being of pesantren, enhancing teacher capacity, and implementing inclusive educational approaches to minimize the potential for radicalization within pesantren communities. This research contributes to a better understanding of radicalism issues in pesantren and provides a foundation for the development of holistic and sustainable policies and prevention programs.